(untitled) (Research, Society and Development, 2020)
The great technological advance followed by the economic and social has sought natural resources to supply such developments. In this case, water resources are a fundamental contribution to such activities, whether in urban or rural areas. Cities were developed on the banks of rivers, with their development in some cases ending up polluting and degrading these natural resources. A great tool for the analysis of damage to water courses can be obtained by applying the Rapid River Assessment Protocols (RAP) and from this it is possible to ascertain how much anthropic activities are or are not pressing this natural resource. When associated to physical-chemical parameters the diagnosis can become more effective. In the present work the stretch of the Antas River in the city of Anápolis was monitored with the PAR from previous studies of Rodrigues 2008 and Guimarães 2012 accompanied by laboratory analysis of physical-chemical parameters. From the same it was possible to ascertain points of degradation and also with correlation of physical-chemical variables. From this study, it is possible to conclude that the RAP is essential to studies of environmental impacts for water bodies.